Perception study of the conservation and utilization of Linpan cultural landscape heritage: the case of Dujiangyan City - Umel, Kabilijiang; Zhu, Pingpu; Zhang, Shuyu; Ishikawa, Mikiko; Yu, Liang (Journal of Environmental Engineering and Landscape Management, 2024)
Linpan has a long history of over 2,300 years and is a unique cultural landscape heritage of the Chengdu Plain derived from the Dujiangyan hydraulic engineering. As urbanization has gradually degraded the Linpan landscape over the past decades, the government is helping to revitalize the local countryside by preserving it. The purpose of this study was to understand the perceptions of Linpan indigenous villagers about its conservation and use, and to investigate the differences in their perceptions and the factors influencing them. The city of Dujiangyan, located at the source of the Dujiangyan Irrigation Area, was taken as the case study area, and a questionnaire survey and quantitative analysis were adopted. The study shows that Linpan indigenous villagers generally support the protection of water systems and fields; Linpan’s vacation and health and wellness functions are recognized by villagers; and regarding Linpan land use, villagers generally prefer to take the form of land market transfer and are willing to transfer arable land and homestead. This also confirms differences in the villagers’ perceptions of the conservation and utilization of Linpan in different locations due to their divergent characteristics. This study provides a reference for the villagers’ perspective on the planning and action of Linpan conservation and use, suggesting the importance of villagers’ distinguishing factors in cultural landscape revitalization.